2015
DOI: 10.1007/s11010-015-2398-y
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia down-regulates cGMP-dependent protein kinase I expression in first trimester cytotrophoblast cells

Abstract: Diabetes in pregnancy is associated with microvascular complications and a higher incidence of preeclampsia. The regulatory signaling pathways involving nitric oxide, cGMP, and cGMP-dependent protein kinase (PKG) have been shown to be down-regulated under diabetic conditions and contribute to the pathogenesis of vascular complications in diabetes. The present study was undertaken to investigate how high glucose concentrations regulate PKG expression in cytotrophoblast cells (CTBs). Human CTBs (Sw. 71) were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…In this study, we focused on the expression of PKG2 in vitro and discovered that it was downregulated in diabetic-stimulated osteoblasts, which was proved by western blot and immunofluorescence. Similar to phenomenon appeared in osteoblasts, several studies have indicated the reduced PKG expression in cardiomyocytes [15,36] and cytotrophoblast cells [37] under diabetic conditions. In order to determine if promoting PKG2 expression is sufficient to protect osteoblasts from diabetes-induced dysfunction, we increased its activity by transfecting lentivirus and adding cinaciguat.…”
Section: Discussionsupporting
confidence: 67%
“…In this study, we focused on the expression of PKG2 in vitro and discovered that it was downregulated in diabetic-stimulated osteoblasts, which was proved by western blot and immunofluorescence. Similar to phenomenon appeared in osteoblasts, several studies have indicated the reduced PKG expression in cardiomyocytes [15,36] and cytotrophoblast cells [37] under diabetic conditions. In order to determine if promoting PKG2 expression is sufficient to protect osteoblasts from diabetes-induced dysfunction, we increased its activity by transfecting lentivirus and adding cinaciguat.…”
Section: Discussionsupporting
confidence: 67%
“…PKG1 is predominantly expressed in cardiovascular tissues, whereas the expression of PKG2 is generally restricted to the brain, intestine, and kidneys (28), indicating that PKG1 may be more important than PKG2 in VSMC function associated with cardiovascular homeostasis. It has been demonstrated that PKG1 was down-regulated in pathological conditions of various cardiovascular disorders (4,7). Indeed, PKG1 expression was decreased in neointimal smooth muscle cells of swine and rat coronary arteries after balloon catheter injury (29,30), and this pathological process was blunted by adenoviral PKG1 gene delivery (30).…”
Section: Discussionmentioning
confidence: 99%
“…In physiological states, the sequential activation of the NO/cGMP/PKG1 pathway by communication between endothelial cells and VSMCs plays a key role in vascular homeostasis and remodeling. However, impairment of this pathway is directly associated with various vascular disorders, such as atherosclerosis, hypertension, and preeclampsia (2)(3)(4).…”
Section: Cgmp-dependent Protein Kinase 1 (Pkg1) Plays An Important Romentioning
confidence: 99%
“…Our understanding of the active mechanisms in placental cells involved in pregnancy adaptations and their response to high glucose concentrations remains limited. Studies have shown that trophoblast cells exposed to high glucose exhibit the downregulation of cGMP‐dependent PKG, which may contribute to the vascular complications observed in diabetic mothers (Nguyen et al., 2015 ). Pathological changes in placental tissues have also been linked to issues with trophoblast viability and proliferation, indicating the impact of high glucose on the miR‑137/PRKAA1/IL‑6 axis (Peng et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%